Academic Practices to Gain and Maintain Student-Teacher Connectedness and Classroom Behavioral Management, Related to Educator Demographics - Kendall, Leslie Threadgill (Lindenwood University, 2016)
Connectedness and classroom management has been defined as the ability to relate to students and keep order and maintain successful relationships with individuals. This qualitative study utilized surveys, questionnaires, interviews, and observations to examine the best practices implemented by educators to develop and maintain connections with students based upon the age, gender, ethnicity, and experience of a studied educator. The research investigated how classroom management positively and/or negatively affected the educator, students, and classroom environment, with respect to connectedness, as evidenced by behaviors such as off-task, aggressive, and non-academically productive behaviors. The research also examined how a teacher’s intonation and delivery method affected behavioral management, as measured by on-task, academically productive, and nonaggressive behaviors. The research examined what was the self-perception of participants of effectiveness in the classroom, as related to the recorded characteristics of age, gender, ethnicity, and experience level. The research focused upon 12 educators in a suburban district and observed the interactions and practices throughout an academic school year. Classroom observations were conducted and results triangulated to determine how connectedness and classroom management was achieved in the classrooms of teachers who represented various ages, genders, ethnicities, and experience levels. The findings concluded that age and experience were crucial in the development and maintenance of connectedness and classroom management. Another finding was the practice in which African American and Caucasian teachers approached connectedness and classroom management varied.